Changes In Glutamic Oxaloacetic Transaminase Serum (SGOT) and Glutamic Pyruvic Transaminase Serum (SGPT) Value In Laparoscopic Cholecystectomy Patient at USU Hospital - Aziizah Gita; Muhar, Adi Muradi (Talenta Publisher, 2020)
Background. Laparoscopic cholecystectomy has become more widely used choice compared to laparotomy cholecystectomy. Laparoscopic cholecystectomy has now become the gold standard of abdominal surgery for abdominal surgery for gallbladder abnormalities, more than 90% of patients with gallstone disease are treated surgically by laparoscopy, but several studies have revealed an increase in SGOT &SGPT values in these surgical procedures. SGPT itself occurs due to the procedure of laparoscopy. In the procedure, there is a temporary increase in the pneumoperitoneum, the pressure on the pneumoperitoneum and its duration affect the severity of ischemia by causing an increase in this liver enzyme. Among several studies, one of them revealed that at 48 hours after laparoscopic cholecystectomy surgery an enzyme increase. Objective. The purpose of the study, this research was conducted to see the changes in SGOT & SGPT values in laparoscopic cholecystectomy surgery. Method. This research method is analytic with cross sectional study design conducted at North Sumatera University Hospital. This research was conducted by looking at secondary data, namely the medical record of patients with gallstones who underwent laparoscopic cholecystectomy surgery from January 2019 to November 2019. The sample was selected by using total sampling method. Data were then analyzed using statistical application software. The number of samples was 45 samples with a diagnosis of gallstones who performed laparoscopic cholecystectomy. Results. Wilcoxon test results showed a significant change between SGOT and SGPT levels before performing operations with SGOT and SGPT levels after surgery with p=0.000 (p<0,05). Conclusion. There are changes in SGOT & SGPT in laparoscopic cholecystectomy.